LiDAR applications in precision agriculture for cultivating crops: A review of recent advances - Rivera, Gilberto; Porras, Raúl; Florencia, Rogelio; Sánchez-Solís, J. Patricia (Computers and electronics in agriculture, 2023)
In recent years, Light Detection and Ranging (LiDAR) technology has been one of the most innovative subjects in laser scanning, remote sensing, and object detection systems. This technology may be popular because it can pinpoint structures or zones of interest in millimetre detail. It can also highlight variations and irregularities, such as surface degradation and vegetation growth. This paper presents a review of the specialised literature on LiDAR systems applied to precision agriculture; specifically, in cultivating crops. First, some preliminaries of LiDAR systems according to the mode of transport used, considering terrestrial, mobile, and aerial laser scanners, are given. Subsequently, a well-organised taxonomy of recent LiDAR applications based on the activity being performed is presented. Here, the following four categories are considered: (1) crop-related metric estimation, (2) tree and plant digitisation, (3) vision systems for object detection and navigation, and (4) planning and decision support. Lastly, we discuss some current trends and research challenges in applying LiDAR technology to cultivation activities in accordance with the state-of-the-art literature. •Compared with photogrammetry, LiDAR technology often obtains more precise 3D models.•Voxelisation is reasonably accurate when applied to tree digitisation.•The crop’s health status is often monitored by estimating the NDVI, LAI or height.•The sunlight index and wood volume are adequate for evaluating pruning structures.•The most used LiDAR sensors are VLP-16, LMS400/111/511, UTM-30LX, and Focus X330.